Research on Numerical Simulation of Tantalum Explosively Formed Projectile Forming Driven by Detonation - Yajun Wang; Weibing Li; Jiaxin Yu; Wenbin Li; Heyang Xu (Shock and Vibration)
In order to study the formation characteristics of tantalum explosively formed projectile (EFP), based on LS-DYNA finite-element software, this article analyzes the influence of mesh size on tantalum EFP forming, compares the accuracy of JC constitutive parameters in different literature on the characterization of tantalum EFP forming, calculates the effective action time of detonation that drives EFP formation, and carries out experimental verification. The results show that the EFP forming velocity was less sensitive to grid size; however, the EFP shape was highly sensitive to grid size, among which the liner had the greatest influence. Besides, for the same density and different constitutive parameters, the velocity of the stabilized EFP was the same, but the change trend of velocity was different, which led to the difference in morphology. The verification test showed that a selection of appropriate JC constitutive parameters could simulate tantalum EFP forming. Finally, the effect of detonation products on EFP forming was reflected mainly in the axial acceleration and radial contraction of the tail skirt. The influence of explosives and detonation products on EFP forming can be ignored 80 μs after the charge detonates. In this work, the numerical simulation method of tantalum EFP forming was studied, which provides guidance for the design and engineering application of tantalum EFP.